Asystentura seksualna – (nie)etyczny seks - Waszyńska, Katarzyna (Studia Edukacyjne, 2019)
Sexuality of people with disabilities is an extremely important topic both from a psychopedagogical and health or socio-cultural perspective. Lack of public awareness, sex education and existing myths make it difficult to meet the sexual needs of these people. In addition, people with disabilities experience hysiological and anatomical limitations and also have problems finding a partner. Some of them decide to contact sex workers. One of the proposed solutions is to introduce the profession of sexual assistant (the so-called Sexual accompaniment). The purpose of this article is to describe the role of sexual assistants and the scope of their functioning in various countries as well as to indicate the benefits and restrictions associated with the introduction of this profession.